2022
DOI: 10.24028/gzh.v43i6.251555
|View full text |Cite
|
Sign up to set email alerts
|

Palаeomagnetism of the Vendian traps of Volyn, southwestern margin of the East European platform. P. 1: palаeomagnetic directions and poles

Abstract: In Earth’s geological evolution the Vendian is significant because: 1) it preceded the «Cambrian Evolutionary explosion» when the multicellular organisms became suddenly much more diverse; 2) it is associated with the global tectonic and palaeogeographic restructuring of supercontinents, a change in geomagnetic field generation and other global processes affecting different layers of the Earth. At the same time, recent publications indicate an extremely irregular behavior of the geomagnetic field in the Vendia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(15 citation statements)
references
References 3 publications
2
13
0
Order By: Relevance
“…We present new results of palaeomagnetic studies of the Vendian (Ediacaran) rocks of the Volyn Basalt Province revealed by six boreholes on the NW Ukraine. This is a continuation of previous studies of upper part of the Volyn series described by Bakhmutov et al [2021]. In the recent works [Shcherbakova et al, 2020;Thallner et al, 2022], the results of palaeointensity determinations of the Volyn series basalts showed the ultra-low dipole moment of Earth's magnetic field which coincident with other palaeomagnetic data for Ediacaran indicating an extremely weak geomagnetic field.…”
supporting
confidence: 87%
See 4 more Smart Citations
“…We present new results of palaeomagnetic studies of the Vendian (Ediacaran) rocks of the Volyn Basalt Province revealed by six boreholes on the NW Ukraine. This is a continuation of previous studies of upper part of the Volyn series described by Bakhmutov et al [2021]. In the recent works [Shcherbakova et al, 2020;Thallner et al, 2022], the results of palaeointensity determinations of the Volyn series basalts showed the ultra-low dipole moment of Earth's magnetic field which coincident with other palaeomagnetic data for Ediacaran indicating an extremely weak geomagnetic field.…”
supporting
confidence: 87%
“…order of magnitude weaker than the presentday field (see references in [Shcherbakova et al, 2020;Bakhmutov et al, 2021]).…”
mentioning
confidence: 93%
See 3 more Smart Citations